Dirichlet conditions at infinity for parabolic and elliptic equations. (June 2016) - Kamin, Shoshana; Punzo, Fabio
Abstract: We investigate existence and uniqueness of bounded solutions of parabolic equations with unbounded coefficients in R N × R + . Under specific assumptions, we establish existence of solutions satisfying prescribed conditions at infinity, depending on the direction along which infinity is approached. Moreover, the large-time behavior of such solutions is addressed. We consider also elliptic equations in R N with similar conditions at infinity.